A Framework to Investigate the Effects of Observation Error on Neural Network Predictions of Fish Age - Derek W. Chamberlin; Thomas E. Helser; John D. Brogan; Irina M. Benson; Jason Conner; Andrew T. Chin; Christopher M. Gburski; Mary Elizabeth Matta; Julie A. Pearce; Kali R. Stone; Todd T. TenBrink; Morgan B. Arrington (Fish and Fisheries, 2026)
Technological innovations for predicting fish age represent a paradigm shift from conventional age estimation methods used in fisheries science. Recently developed secondary methods rely on models trained on conventional age estimates, derived from subjective interpretation of growth patterns and a biological property of the fish to predict age. Hence, quantifying the error that propagates from these models and the conventional age estimates on which they are trained is critical to fully account for uncertainty in predicted ages used in fisheries stock assessments. We review the development of three secondary age prediction methods: image analysis, epigenetics and Fourier transform near‐infrared spectroscopy (FT‐NIRS); the use of artificial intelligence (AI) within each method; and present an approach to examine the effects of ageing error on AI age prediction models. As a case study, we conducted an empirical study, coupled with simulation, to quantify the effects of ageing error on the performance of a multimodal convolutional neural network (MMCNN) model used to predict eastern Bering Sea walleye pollock ( Gadus chalcogrammus ) ages from otoliths analysed using FT‐NIRS. Results indicated repeatability of predicted ages was high between instrument operators, while adding ageing error resulted in a slight decrease in model performance from R 2 = 0.92 and CV = 7.6% to R 2 = 0.87 and CV = 10.2% on test datasets. Our results also suggest the MMCNN model is robust to noise in calibration age data and model performance may be better than performance metrics indicate when the model is evaluated against data with increased error.

Decoupled responses of mycorrhizal fungal communities and function to recurrent wildfire - Solomon Maerowitz-McMahan; Christopher E. Gordon; Rachael H. Nolan; Pushpinder Matta; Amaia Montalban de la Mata; Jeff R. Powell (Soil Biology and Biochemistry, 2026)

Deep fresh groundwater in offshore islands of Bangladesh and its implications for climate-resilient groundwater management in coastal aquifers - Naymur Rahman; Kazi Matin Ahmed; Vijay Matta; Pavel Khan; Fuad Hasan; Bodruddoza Mia; Tareq Chowdhury; Anwar Zahid; Aynul Huda; Mahfuzur R. Khan (Hydrogeology Journal, 2026)

Retrieval of snow liquid water content from radiative transfer model, field data and PRISMA satellite data - C. Ravasio; R. Garzonio; B. Di Mauro; E. Matta; C. Giardino; M. Pepe; E. Cremonese; P. Pogliotti; C. Marin; R. Colombo (Remote Sensing of Environment, 2024)

A review of the Pacific sleeper shark Somniosus pacificus: biology and fishery interactions - Mary Elizabeth Matta; Cindy A. Tribuzio; Lindsay N. K. Davidson; Keith R. Fuller; Garrett C. Dunne; Allen H. Andrews (Polar Biology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Assessment of metal enrichment and contamination in surface sediment of Mandovi estuary, Goa, West coast of India - Cynthia V. Gaonkar; Maheshwar R. Nasnodkar; Vishnu Murty Matta (Environmental Science and Pollution Research, 2021)

HPI appraisal of concentrations of heavy metals in dynamic and static flow of Ganga River System - Gagan Matta; Avinash Kumar; A. K. Tiwari; Pradeep K. Naik; R. Berndtsson (Environment, Development and Sustainability, 2020)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

How Bad Is Aluminum Exposure to Reproductive Parameters in Rats? - Viviane G. S. Mouro; Tatiana P. Menezes; Graziela D. A. Lima; Rafael R. Domingues; Ana Cláudia F. Souza; Juraci A. Oliveira; Sérgio L. P. Matta; Mariana Machado-Neves (Biological Trace Element Research, 2018)

Assessment of physicochemical characteristics of Ganga Canal water quality in Uttarakhand - Gagan Matta; Sachin Srivastava; R. R. Pandey; K. K. Saini (Environment, Development and Sustainability, 2017)

Biofiltration vs conventional activated sludge plants: what about priority and emerging pollutants removal? - R. Mailler; J. Gasperi; V. Rocher; S. Gilbert-Pawlik; D. Geara-Matta; R. Moilleron; G. Chebbo (Environmental Science and Pollution Research, 2014)

Phylogenetic analysis of canine parvovirus partial VP2 gene in India - H. K. Mukhopadhyay; Samyukta Lakshmi Matta; S. Amsaveni; P. X. Antony; J. Thanislass; R. M. Pillai (Virus Genes, 2014)

Effect of Low-Temperature Storage on Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae) - R J Silva; F J Cividanes; E C Pedroso; J C Barbosa; D H Matta; E T Correia; A K Otuka (Neotropical Entomology, 2013)

Assessing Public Preferences for Forest Biomass Based Energy in the Southern United States - Andres Susaeta; Janaki Alavalapati; Pankaj Lal; Jagannadha R. Matta; Evan Mercer (Environmental Management, 2010)

Structure–activity studies of Ti(IV) complexes: aqueous stability and cytotoxic properties in colon cancer HT-29 cells - Ramón Hernández; José Lamboy; Li Ming Gao; Jaime Matta; Félix R. Román; Enrique Meléndez (JBIC Journal of Biological Inorganic Chemistry, 2008)

Age, growth, maturity, and mortality of the Alaska skate, Bathyraja parmifera, in the eastern Bering Sea - Mary Elizabeth Matta; Donald R. Gunderson (Environmental Biology of Fishes, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Associations between metals and the blue mesogleal protein of Cassiopea xamachana - M. A. Phelan; J. L. Matta; Y. M. Reyes; R. Fernando; R. A. Boykins; R. S. Blanquet (Marine Biology, 2006)

Susceptibility profile of vaginal yeast isolates from Brazil - M.A. Ribeiro; R. Dietze; C.R. Paula; D.A. Da Matta; A.L. Colombo (Mycopathologia, 2001)

Water production functions in kiwi - E. A. Holzapfel; R. Merino; M. A. Mariño; R. Matta (Irrigation Science, 2000)

Heavy metals, lipid peroxidation, and ciguatera toxicity in the liver of the caribbean barracuda (Sphyraena barracuda) - J. Matta; M. Milad; R. Manger; T. Tosteson (Biological Trace Element Research, 1999)

Effect of a Polychlorinated Biphenyl Metabolite on Early Life Stage Survival of Two Species of Trout - M. B. Matta; C. Cairncross; R. M. Kocan (Bulletin of Environmental Contamination and Toxicology, 1997)

Toxicity of weathered coal tar for shortnose sturgeon (Acipenser brevirostrum) embryos and larvae - R. M. Kocan; M. B. Matta; S. M. Salazar (Archives of Environmental Contamination and Toxicology, 1996)

Nutrient dynamics during the first three years of an alleycropping agroecosystem in southern USA - R. P. Matta-Machado; C. F. Jordan (Agroforestry Systems, 1995)